2012
DOI: 10.1089/ten.tea.2012.0097
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Microgravity-Bioreactor Cultivation Enhances the Hepatic Differentiation of Mouse Embryonic Stem Cells on Biodegradable Polymer Scaffolds

Abstract: Embryonic stem (ES) cells are pluripotent cells that are capable of differentiating all the somatic cell lineages, including those in the liver tissue. We describe the generation of functional hepatic-like cells from mouse ES (mES) cells using a biodegradable polymer scaffold and a rotating bioreactor that allows simulated microgravity. Cells derived from ES cells cultured in the three-dimensional (3D) culture system with exogenous growth factors and hormones can differentiate into hepatic-like cells with morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…To the best of our knowledge, although a few studies have examined the formation and multiple-tissue or tissue-specific differentiation of EBs in a RCCS [15,34,35], no one has reported the hepatic differentiation of mES cells via EB formation in a rotating bioreactor. In our previous study [20], the hepatic differentiation of mES cells within the 3D condition of a rotating bioreactor has been described, which is similar to the present study. A 3D-culture system consisted of biodegradable scaffolds, growth-factor-reduced Matrigel, and a rotating bioreactor in our previous study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…To the best of our knowledge, although a few studies have examined the formation and multiple-tissue or tissue-specific differentiation of EBs in a RCCS [15,34,35], no one has reported the hepatic differentiation of mES cells via EB formation in a rotating bioreactor. In our previous study [20], the hepatic differentiation of mES cells within the 3D condition of a rotating bioreactor has been described, which is similar to the present study. A 3D-culture system consisted of biodegradable scaffolds, growth-factor-reduced Matrigel, and a rotating bioreactor in our previous study.…”
Section: Discussionsupporting
confidence: 81%
“…In our prior study, we demonstrated that the growth and differentiation of ES cells in a biodegradable polymer scaffold within a rotating microgravity bioreactor yields organized functional hepatocytes that can be used in research on bioartificial livers and engineered liver tissue [20]. Therefore, we hypothesized that a rotating bioreactor could be used for the efficient large-scale differentiation of ES cells into hepatocytes, which may further serve as an ideal source of cells for both hepatocyte transplantation and the creation of bioartificial livers.…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence supports the notion that culture vessel rotation in the dynamic bioreactor reduces the occurrence of sedimentation and maintains the cells suspended in a relatively stable “free fall” condition that circumvents the harmful effects associated to shear stress . In addition, the presence of a gas exchange membrane in the culture chamber favors the optimal oxygenation of thick cell‐based constructs or microbeads encapsulated cells, preventing the formation of central core necrosis . For what concerns the encapsulation of the cells into microbeads, it is important to underline that encapsulation technology may contribute to the success of cell transplantation allowing a more efficient and functional integration of cells in tissue regenerative approaches .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, lowering shear stress in rotating wall vessels was found to favor MSC adipogenesis (Meyers et al 2005) as well as hepatogenic differentiation of ESCs (Fig. 1) (Wang et al 2012).…”
Section: Rotating Wall Vesselmentioning
confidence: 98%